1990
DOI: 10.1056/nejm199001183220304
|View full text |Cite
|
Sign up to set email alerts
|

The Risk ofPneumocystis cariniiPneumonia among Men Infected with Human Immunodeficiency Virus Type 1

Abstract: We assessed the risk of pneumonia due to Pneumocystis carinii in 1665 participants in the Multicenter AIDS Cohort Study who were seropositive for human immunodeficiency virus type 1 (HIV-1) but did not have the acquired immunodeficiency syndrome (AIDS) and were not receiving prophylaxis against P. carinii. During 48 months of follow-up, 168 participants (10.1 percent) had a first episode of P. carinii pneumonia. The risk was greatly increased in participants with CD4+ cell counts at base line of 200 per cubic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
254
0
17

Year Published

1992
1992
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 643 publications
(278 citation statements)
references
References 5 publications
4
254
0
17
Order By: Relevance
“…This score, for selecting patients with a high risk for PCP [2,19], was determined according to the following clinical and laboratory criteria: 5 points were assigned for a peripheral blood CD4 lymphocyte count of <200/AL or AIDS (except Kaposi's sarcoma); 3 points for symptomatic HIV infection without AIDS; and 2 points for Kaposi's sarcoma, a CD4 lymphocyte count of 200-500/AL, or positivity for HIV p24 antigen in serum. Previous PCP, previous prophylaxis with aerosolized pentamidine, and simultaneous antiretroviral treatment were allowed in the study protocol.…”
Section: Study Populationmentioning
confidence: 99%
“…This score, for selecting patients with a high risk for PCP [2,19], was determined according to the following clinical and laboratory criteria: 5 points were assigned for a peripheral blood CD4 lymphocyte count of <200/AL or AIDS (except Kaposi's sarcoma); 3 points for symptomatic HIV infection without AIDS; and 2 points for Kaposi's sarcoma, a CD4 lymphocyte count of 200-500/AL, or positivity for HIV p24 antigen in serum. Previous PCP, previous prophylaxis with aerosolized pentamidine, and simultaneous antiretroviral treatment were allowed in the study protocol.…”
Section: Study Populationmentioning
confidence: 99%
“…Patients with depleted CD4 cell counts less than 200 cells/mm 3 are more likely to develop Pneumocystis jiroveci pneumonia (PJP) amongst various other opportunistic infections. 21 The Centres for Disease Control and Prevention (CDC) advocates primary prophylaxis with co-trimoxazole for adults whose CD4 cell count is less than 200 cells/mm 3 . 22 The majority of patients with CD4 counts of < 200 cells/mm 3 who were treated with PJP had a mortality of between 20% and 40%; this is further increased to 60% in PJP patients who are intubated (Guidelines for Prevention and Treatment of Opportunistic Infections in HIV-Infected Adults and Adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…In the ASD study the CD4 count among persons developing PCP while receiving cART was low (median=29 cells/µL), and was lower among those not taking cART (median=13 cells/µL) [11]. The prospective pan-European EuroSIDA study reported that the median CD4 count was 30 cells/µL among persons developing PCP while receiving cART, and was similar among those not receiving cART who got PCP [8]. Patients without improvement in their CD4 count after starting cART remain at risk for PCP.…”
Section: Before the Onset Of The Aids Epidemic Pcp Was Uncommon In Thmentioning
confidence: 99%
“…During the early years of the AIDS epidemic, PCP accounted for two thirds of AIDS-defining illness in patients in the United States, and an estimated 75% of HIV-infected patients developed PCP during their lifetime [6] [7]; rates of PCP were as high as 20 per 100 person-years among those with CD4 cell counts <200 cells/µL [7] [8].…”
Section: Before the Onset Of The Aids Epidemic Pcp Was Uncommon In Thmentioning
confidence: 99%